Cobimetinib- and vemurafenib-induced granulomatous dermatitis and erythema induratum: A case report. (May 2019) - Iafolla, Marco AJ; Ramsay, Jennifer; Wismer, Judy; McWhirter, Elaine
Metastatic melanoma is an aggressive malignancy. Survival can be increased with the combination of BRAF and MEK inhibition. BRAF inhibitor-induced cutaneous toxicities can be attenuated with MEK inhibition. Here, we describe the first reported case of a patient with metastatic melanoma who developed granulomatous dermatitis and erythema induratum when treated with combination BRAF (vemurafenib) and MEK inhibitor (cobimetinib) therapy and discuss the clinical features and management of dermatologic side-effects secondary to BRAF +/– MEK inhibition.